Differentiating inflamed and normal lungs by the apparent reaction rate constants of lactate dehydrogenase probed by hyperpolarized 13C labeled pyruvate - Xu, He N.; Kadlececk, Stephen; Shaghaghi, Hoora; Zhao, Huaqing; Profka, Harilla; Pourfathi, Mehrdad; Rizi, Rahim; Li, Lin Z. (Quantitative Imaging in Medicine and Surgery, 2016)
Background: Clinically translatable hyperpolarized (HP) 13C-NMR can probe in vivo enzymatic reactions, e.g., lactate dehydrogenase (LDH)-catalyzed reaction by injecting HP 13C-pyruvate into the subject, which is converted to 13C labeled lactate by the enzyme. Parameters such as 13C-lactate signals and lactate-to-pyruvate signal ratio are commonly used for analyzing the HP 13C-NMR data. However, the biochemical/biological meaning of these parameters remains either unclear or dependent on experimental settings. It is preferable to quantify the reaction rate constants with a clearer physical meaning. Here we report the extraction of the kinetic parameters of the LDH reaction from HP 13C-NMR data and investigate if they can be potential predictors of lung inflammation. Methods: Male Sprague-Dawley rats (12 controls, 14 treated) were used. One dose of bleomycin (2.5 U/kg) was administered intratracheally to the treatment group. The lungs were removed, perfused, and observed by the HP-NMR technique, where a HyperSense dynamic nuclear polarization system was used to generate the HP 13C-pyruvate for injecting into the lungs. A 20 mm 1H/13C dual-tuned coil in a 9.4-T Varian vertical bore NMR spectrometer was employed to acquire the 13C spectral data every 1 s over a time period of 300 s using a non-selective, 15-degree radiofrequency pulse. The apparent rate constants of the LDH reaction and their ratio were quantified by applying ratiometric fitting analysis to the time series data of 13C labeled pyruvate and lactate. Results: The apparent forward rate constant kp=(3.67±3.31)×10−4 s−1, reverse rate constant kl=(4.95±2.90)×10−2 s−1, rate constant ratio kp/kl=(7.53±5.75)×10−3 for the control lungs; kp=(11.71±4.35)×10−4 s−1, kl=(9.89±3.89)×10−2 s−1, and kp/kl=(12.39±4.18)×10−3 for the inflamed lungs at the 7th day post treatment. Wilcoxon rank-sum test showed that the medians of these kinetic parameters of the 7-day cohort were significantly larger than those of the control cohort (P